Role of serum LDH in preeclampsia as a prognostic factor – a cross sectional case control study in tertiary care hospital - Mary, Vinitha Padmini; Chellatamizh, M.; Padmanaban, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: LDH is an intracellular cytoplasmic enzyme. It is ubiquitous to all the major organ systems. Cellular enzymes in extracellular space have no metabolic function, although they serve as indicators of disturbances in cellular integrity. Serum LDH is abnormal in many disorders, therefore total serum LDH is highly sensitive but nonspecific test. In preeclampsia also LDH may be elevated and can indicate the prognosis for both mother and fetus. We conducted this study to examine the relationship between lactate dehydrogenase concentration and the severity of the disease and the occurrence of its complications. Methods: 200 pre-eclamptic women (121 with mild and 79 with severe pre-eclampsia) and 200 healthy normotensive controls were studied prospectively at Government Kilpauk medical college and hospital between January and December 2015. Demographic, hemodynamic, and laboratory data were compared among the three groups. The symptoms and complications of severe pre-eclampsia along with fetal outcome were analyzed according to the levels of LDH. Results: Severely pre-eclamptic patients were significantly younger, with low gravidity and parity. On the other hand, they had significantly increased systolic and diastolic pressure and liver enzymes, uric acid, urine albumin, and LDH levels. The symptoms and complications of pre-eclampsia along with perinatal mortality were increased significantly in patients with LDH >800 IU/l compared with those who had lower levels. Conclusions: Lactate dehydrogenase is a useful biochemical marker that reflects the severity of pre-eclampsia. In our study, LDH has been evaluated as a biochemical marker for preeclampsia and as a prognosticator of the disease severity. Detection of high-risk patients with increased levels of LDH mandate close monitoring and management to prevent maternal and fetal morbidity and mortality.